2019
DOI: 10.1111/cge.13565
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of MidXq28‐duplication syndrome distal to MECP2 and proximal to RAB39B genes

Abstract: Two distinct genomic disorders have been linked to Xq28‐gains, namely Xq28‐duplications including MECP2 and Int22h1/Int22h2‐mediated duplications involving RAB39B. Here, we describe six unrelated patients, five males and one female, with Xq28‐gains distal to MECP2 and proximal to the Int22h1/Int22h2 low copy repeats. Comparison with patients carrying overlapping duplications in the literature defined the MidXq28‐duplication syndrome featuring intellectual disability, language impairment, structural brain malfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…First, spastic paralysis of both lower limbs starts around puberty, causing difficulty in climbing stairs and requiring surgical intervention. In R2 duplications, 6 of 15 cases (Vandewalle et al reported three of seven cases [ 8 ], Ward et al reported one of three cases [ 9 ], and Sinibald et al reported two of five cases [ 10 ]) exhibited pyramidal tract signs or spasticity (including a description of toe walking that required heel cord lengthening). R2 contains GDI1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, spastic paralysis of both lower limbs starts around puberty, causing difficulty in climbing stairs and requiring surgical intervention. In R2 duplications, 6 of 15 cases (Vandewalle et al reported three of seven cases [ 8 ], Ward et al reported one of three cases [ 9 ], and Sinibald et al reported two of five cases [ 10 ]) exhibited pyramidal tract signs or spasticity (including a description of toe walking that required heel cord lengthening). R2 contains GDI1 .…”
Section: Discussionmentioning
confidence: 99%
“…Third, abnormalities in intracranial findings of the head, including microcephaly, are as follows: In R2 duplications, 11 of 15 cases (Vandewalle et al reported four of seven cases [ 8 ], Ward et al reported three of three cases [ 9 ], and Sinibald et al reported four of five cases [ 10 ]) presented with corpus callosum hypoplasia, and brainstem and cerebellar vermis hypoplasia with ventricular dilatation, suggesting that R2 duplications may cause dysgenesis of the brain during the embryonic period [ 18 ]. Yamamoto et al [ 7 ] and Honda et al [ 19 ] stated that duplication of the GDI1 region is associated with hypoplasia of the corpus callosum in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that Xq28 duplications involving the ID-associated filamin A gene ( FLNA ; 300017) contribute to the presence of chronic constipation [ 17 ], as FLNA point mutations have been found in families with pseudointestinal obstruction [ 128 , 129 ]. Against this hypothesis is that constipation was not a feature in recent case studies on patients harbouring a Xq28 duplication involving FLNA without MECP2 [ 42 , 63 , 130 , 131 ]. The presence of Hirschsprung disease in MDS, although rare, has also been suggested to be linked to dysregulated levels of the L1CAM gene (which can be implicated in Xq28 duplications) as L1CAM mutations have been detected in patients with X-linked hydrocephalus with Hirschsprung disease [ 22 , 132 , 133 ].…”
Section: The Syndromic Phenotype Of Mecp2 Duplicat...mentioning
confidence: 99%
“…It was recently found that for individual with MDS, a larger duplication size correlates with greater phenotype severity, and greater phenotype severity was associated with the inclusion of RAB39B duplication (Peters et al, 2019). Interestingly, duplications occurring distal to MECP2 and proximal to RAB39B , termed MidXq28‐duplication syndrome, are also presented with features such as ID, epilepsy, brain malformations including microcephaly and minor craniofacial features (Sinibaldi et al, 2019). Duplication of genes other than MeCP2 and RAB39B , including those encoding FLNA, RPL10, and GDI1 located in this region, could therefore also contribute to MDS phenotypes.…”
Section: Introductionmentioning
confidence: 99%